Analisis Kesulitan Mengajar Guru Kelas Pada Mata Pelajaran IPA Di MI Islamiyah Sidoarjo - Wakhidah, Nur (Journal Of Islamic Elementary School (JIES), 2016)
Natural science includes many concepts of abstract and difficult, so it is difficult to understand. Average teachers MI have educational backgrounds PAI so understanding the concept of IPA is relatively low. The concept that is understood is only the concept that there is a book IPA in MI. Rarely teachers do practical whereas a lot of the media of the nature which can be used as a medium of learning. As a result, most teachers are able to develop their critical thinking, including rarely guided students in the process of thinking and develop skills in the process. The factors cause difficulty teaching the teacher is not the appropriate educational backgrounds, lack of laboratory facilities and a lack of training and KKG and lack of support from the school. IPA material is difficult to understand the teacher is a matter of style, function and parts of a plant, the reproduction of living beings. How to overcome the difficulties of teaching science is putting teachers with appropriate educational backgrounds, a teacher active in KKG and training.